2016
DOI: 10.1039/c5gc01436k
|View full text |Cite
|
Sign up to set email alerts
|

A simple process for lignin nanoparticle preparation

Abstract: The lack of renewable resources and their inefficient use is a major challenge facing the society. Lignin is a natural biopolymer obtained mainly as a by-product from pulp-and paper-making industry, and is primarily burned to produce energy. However, the interest for using lignin in more advanced applications has increased rapidly. In particular, lignin based nanoparticles could find potential use in functional surface coatings, nanoglues, drug delivery, and microfluidic devices. In this work, a straightforwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
497
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 509 publications
(532 citation statements)
references
References 26 publications
(44 reference statements)
22
497
4
1
Order By: Relevance
“…Figueiredo et al [37] used the same method as described above including identical lignin [34]. The dynamic light scattering results revealed an average hydrodynamic radius of 221 ± 10 nm, which is in good agreement with the results obtained by Lievonen et al [34].…”
Section: Production Of Nano-/microsized Lignin Materialssupporting
confidence: 81%
“…Figueiredo et al [37] used the same method as described above including identical lignin [34]. The dynamic light scattering results revealed an average hydrodynamic radius of 221 ± 10 nm, which is in good agreement with the results obtained by Lievonen et al [34].…”
Section: Production Of Nano-/microsized Lignin Materialssupporting
confidence: 81%
“…1a). The zeta-potential value (also measured by DLS) of the lignin nanoparticle dispersion was −37.5 and −35.8 mV for DLNPs and OLNPs, respectively, which indicated a relative high stability of these two lignin nanoparticles in water [7]. The uniform particle size, regular-sphere structure, and high stability of these two lignin nanoparticles indicated that they might be promising candidates for the production of nanocomposite films with PVA polymer.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…KL obtained from the black liquor in the pulping process differs from native lignin substantially in monomer composition, molar mass, reactivity, and solubility in water and in common solvents . Furthermore, low reactivity, insolubility in water and the presence of aliphatic thiol groups are a major limitation for industrial processing and large‐scale applications, especially to produce hybrid polymer . In this sense, to utilize KL with high efficiency, developing new methods to treat KL is encouraged to increase the reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the redox reaction systems are based on an electron transfer from an electron donor (reducing agent) to an electron acceptor (oxidant agent). A number of investigations have been conducted on the incorporation of KL by polymerization of different monomers and initiators, in order to produce new products by free‐radical polymerization . Some authors reported that the lignin accelerates the polymerization rate due to the existence of phenolic groups and other authors reported that the lignin inhibits the polymerization of vinyl monomers due the macromolecular structure of lignin .…”
Section: Introductionmentioning
confidence: 99%